(untitled) (Raparin Journal of Humanities (RJH), 2023)
his research deals with the place in the novel (The Night of the Fall of Jalawla) by Tahsin Karmyani، to analyze the place in it، reveal its concept، its significance and its relationship to the elements of narration in the novel، and to show its patterns in three groups of places in the form of opposite dualities represented in the sympathetic and hostile place، the closed and open place، the place of movement and residence And this element has an important role in explaining the character’s relationship with the place and its impact on the psychological and emotional state of the novelist.